2012
DOI: 10.3389/fmicb.2012.00261
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Antimycotic Activity of Amphotericin B by Targeting the Oxidative Stress Response of Candida and Cryptococcus with Natural Dihydroxybenzaldehydes

Abstract: In addition to the fungal cellular membrane, the cellular antioxidant system can also be a viable target in the antifungal action of amphotericin B (AMB). Co-application of certain redox-potent natural compounds with AMB actually increases efficacy of the drug through chemosensitization. Some redox-potent chemosensitizers and AMB perturb common cellular targets, resulting in synergistic inhibition of fungal growth. Chemosensitizing activities of four redox-potent benzaldehydes were tested against clinical and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 28 publications
3
22
0
1
Order By: Relevance
“…This would explain the result found by our group, where there is an antagonistic interaction between these thiazoles and amphotericin B against various isolates of C. neoformans and C. gattii (Table 4) (26). Some studies have demonstrated that amphotericin B, in addition to the action on the membrane ergosterol, also acts by promoting an increase in intracellular H 2 O 2 and lipid peroxidation, which helps the fungicide action of this drug and prevents the emergence of resistant organisms (33,34).…”
Section: Discussionsupporting
confidence: 63%
“…This would explain the result found by our group, where there is an antagonistic interaction between these thiazoles and amphotericin B against various isolates of C. neoformans and C. gattii (Table 4) (26). Some studies have demonstrated that amphotericin B, in addition to the action on the membrane ergosterol, also acts by promoting an increase in intracellular H 2 O 2 and lipid peroxidation, which helps the fungicide action of this drug and prevents the emergence of resistant organisms (33,34).…”
Section: Discussionsupporting
confidence: 63%
“…The control of oxidative stress may be a common mechanism for bacterial tolerance (58). It has been reported that targeting of the oxidative stress response of Candida is able to enhance the efficacy of AMB treatment (59). Exposure of C. albicans planktonic cultures to AMB at a concentration equivalent to the MIC might result in the upregulation of multiple proteins involved in oxidative stress adaptation (60).…”
Section: Figmentioning
confidence: 99%
“…AmB lethality can also occur via the inhibition of protein synthesis through loss of intracellular K + and ATP depletion (Alonso et al, 1979). In addition, AmB is known to cause oxidative damage in cells of the pathogenic fungus Candida albicans by generating superoxide anions (Kim et al, 2012). We previously demonstrated that lethal concentrations of AmB caused dramatic disruption of the spherical architecture of vacuoles in Saccharomyces cerevisiae and C. albicans cells, and since then, this AmB-induced intracellular event has been considered the direct cause of its lethality (Borjihan et al, 2009;Ogita et al, 2006;Ogita et al, 2012).…”
Section: Introductionmentioning
confidence: 99%